1998
DOI: 10.1063/1.476453
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polydispersity on hard sphere crystals

Abstract: We use simple models and molecular dynamics simulations to determine the effects of polydispersity δ on the equation of state for hard sphere crystals. Experiments show that the osmotic pressure for poly-(methyl methacrylate) (PMMA) spheres with a poly-(12-hydroxy stearic acid) (PHSA) layer with a 5% polydispersity exceeds the value expected for hard spheres as the volume fraction φ increases, particularly for φ>0.60. Mean field theory predicts a higher osmotic pressure with increasing polydispersity, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
122
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(134 citation statements)
references
References 23 publications
11
122
1
Order By: Relevance
“…[6] has a more detailed bibliography of earlier work. These studies have revealed that, compared to the monodisperse case, polydispersity causes several qualitatively new phenomena.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6] has a more detailed bibliography of earlier work. These studies have revealed that, compared to the monodisperse case, polydispersity causes several qualitatively new phenomena.…”
mentioning
confidence: 99%
“…The effect of polydispersity on the phase behavior of hard spheres has been investigated by experiments [1, 2], computer simulations [3,4,5,6], density functional theories [7,8], and simplified analytical theories [6,9,10,11,12,13,14]; Ref.…”
mentioning
confidence: 99%
“…The formation of a hybrid colloidal film consisting of a mixture of an equal number of two PS spheres (d=300 nm and d=360 nm) artificially broadens the size distribution beyond the polydispersity limit of about 5% necessary for crystallization. [152] Indeed, the crystallization is prohibited in this hybrid colloidal film, as indicated by the lack of a long-range order in the right-hand panel of parently, the crystalline order is a prerequisite for the BG but not for the newly observed lower frequency HG, which is omnidirectional in the colloidal glass. An identification of the latter as a theoretically anticipated HG, [153] through density-of-states (DOS) calculations, [80] is examined in Fig.…”
Section: Band Gaps In Polymer Opals and Disordered Systemsmentioning
confidence: 99%
“…5.6). Since the size difference is clearly below 5%, [152] the particles form random co-crystals during vertical lifting deposition under stirring. Fig.…”
Section: Effective Medium Velocity In Defect Doped Opalsmentioning
confidence: 99%
“…One of the main complications of these systems is that their multi-component character enables coexistence of arbitrarily many fluid or solid phases each accommodating a specific subpopulation of the overall distribution. A prominent example are dense fluids of polydisperse spherical particles where the presence of a range of different sizes may lead to a suppression of crystallization [42,43] in favour of various amorphous states whose nature has been the subject of recent simulation studies [44][45][46]. Alternatively, size polydisperse sphere fluids may develop a coexistence of a number of different solid phases following a pathway referred to as fractionated crystallization [47].…”
Section: Introductionmentioning
confidence: 99%